2011
DOI: 10.1089/cbr.2010.0916
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of 177Lu-Nimotuzumab: A Potential Tool for Radioimmunotherapy of Epidermal Growth Factor Receptor–Overexpressing Tumors

Abstract: (177)Lu-Nimotuzumab was obtained with high purity and specific activities under optimal conditions without significant loss in immunoreactivity and might be a potential radioimmunoconjugate for radioimmunotherapy of tumors with epidermal growth factor receptor overexpression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Nimotuzumab is a human anti‐EGFR monoclonal antibody 28 . It was reported that nimotuzumab combined with radiotherapy and chemotherapy achieved a certain efficacy and was well tolerated in the treatment of advanced nasopharyngeal carcinoma and head/neck squamous cell carcinoma, with low incidence of rash 29,30 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nimotuzumab is a human anti‐EGFR monoclonal antibody 28 . It was reported that nimotuzumab combined with radiotherapy and chemotherapy achieved a certain efficacy and was well tolerated in the treatment of advanced nasopharyngeal carcinoma and head/neck squamous cell carcinoma, with low incidence of rash 29,30 .…”
mentioning
confidence: 99%
“…[24][25][26][27] Nimotuzumab is a human anti-EGFR monoclonal antibody. 28 It was reported that nimotuzumab combined with radiotherapy and chemotherapy achieved a certain efficacy and was well tolerated in the treatment of advanced nasopharyngeal carcinoma and head/neck squamous cell carcinoma, with low incidence of rash. 29,30 This study analyzed the clinical data from 28 advanced NSCLC patients treated in the First Department of Internal Medicine, Tianjin Medical University Cancer Institute and Hospital between February 2009 and June 2010.…”
mentioning
confidence: 99%
“…The specific activities of the radiolabelled agents were comparable to that of similar agents reported in the past for preclinical and clinical studies. Further, it is interesting to note that though we have used 177 Lu produced by direct neutron activation of Lu 2 O 3 (84.6% enriched in 176 Lu) for radiolabelling studies, the specific activity of the radiolabelled mAb is comparable to what was achieved by Vera et al, when NCA 177 Lu was used. NCA 177 Lu is produced by indirect route, wherein an isotopically enriched 176 Yb target undergoes (n, γ) reaction to produce 177 Yb (t ½ = 1.9 h), which subsequently decays by β − emission to yield 177 Lu that can be chemically separated.…”
Section: Discussionmentioning
confidence: 99%
“… Further, it is interesting to note that though we have used 177 Lu produced by direct neutron activation of Lu 2 O 3 (84.6% enriched in 176 Lu) for radiolabelling studies, the specific activity of the radiolabelled mAb is comparable to what was achieved by Vera et al, when NCA 177 Lu was used. NCA 177 Lu is produced by indirect route, wherein an isotopically enriched 176 Yb target undergoes (n, γ) reaction to produce 177 Yb (t ½ = 1.9 h), which subsequently decays by β − emission to yield 177 Lu that can be chemically separated. The specific activity of NCA 177 Lu is several hundred‐fold higher than that of neutron‐activated 177 Lu produced in medium flux research reactors.…”
Section: Discussionmentioning
confidence: 99%
“…[61][62][63][64] In parallel, nimotuzumab was conjugated to radionuclides including 188 Os, 99 mTc, 188 Re and 177 Lu, and some of the resulting immunoradioconjugates entered clinical tests as diagnostic or therapeutic tools for tumors of epidermal origin. [65][66][67][68] Now, approximately 20 phase I-II clinical studies are investigating the efficacy of nimotuzumab for indications as diverse as glioma, head and neck, colorectal and lung cancer. Moreover, nimotuzumab is being evaluated in phase III trials (i) for the therapy of nasopharyngeal and head and neck cancer (HNC), in combination with not better specified chemotherapy and radiation ( Table 3, NCT01074021, NCT00957086); (ii) for the treatment of locally advanced esophageal cancer, in combination with 5-fluorouracil (a pyrimidine analog) and radiotherapy (Table 3, NCT01249352); and (iii) in esophageal cancer patients who suffer with recurrence in regional lymph nodes after esophagectomy, combined with specified chemotherapy and radiation ( Table 3, NCT01402180).…”
Section: Monoclonal Antibodies Under Advanced (Phase Iii-iv) Clinicalmentioning
confidence: 99%